Notes on the identity of Justicia diffusa var. hedyotidifolia (Acanthaceae) with reduction of Justicia gambleana - Soumya, Puliyakode; Sunojkumar, Purayidathkandy (Phytotaxa, 2019)
Taxonomic identity of Justicia diffusa var. hedyotidifolia is discussed and Justicia gambleana is reduced to the synonym. Detailed description, photographs, and distributional notes are provided. The lectotypification of Justicia diffusa var. hedyotidifolia is also discussed.